Ancient Hindu healing methodologies as cornerstones of health and well-being - Neshika Munshi; Raisuyah Bhagwan (Discover Social Science and Health)
Abstract Hinduism is one of the world’s oldest religions which is rich in its healing traditions and practices. Despite this little literature exists on this particular worldview and how Hindu spirituality contributes to well-being. Since ancient times religion and spirituality have been heralded as sources of strength, comfort and resilience to individuals and families, as they transition through life and cope with various forms of physical or psychological distress. This study explored how Hindu beliefs, practices and healing methodologies enables the physical health and mental well-being of individuals and their families. The study was guided by a qualitative research paradigm, with an exploratory design. Non-probability purposive sampling strategies were used to recruit two samples. These participants included seven spiritual leaders and twelve devotees from a large Hindu faith-based organization, in eThekwini, in the Province of KwaZulu-Natal, of South Africa. Data was collected using semi-structured interviews and a focus group discussion with Hindu spiritual leaders and devotees, respectively. Thematic analysis was used to guide the analysis of the data, after it was transcribed verbatim. The study found that Hindu families derive immense psychological, social, health and spiritual benefits through the use and practice of a wide repertoire of Hindu healing methodologies. The study uncovered the value of ancient Hindu beliefs and practices such as yoga, Ayurveda, astrology, meditation, and devotional music and how they strengthened the well-being of individuals and families.